KONDISI PSIKOLOGIS DAN PSIKOSOSIAL SISWA YANG MENGALAMI PERCERAIAN ORANG TUA (CASE STUDY DI SALAH SATU SMK WILAYAH JAKARTA TIMUR) - Desi Nur'aini; Wirda Hanim; Susi Fitri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The role of education in educating the nation's children so that they have solid knowledge and skills must be in line with the development of their psychology so that their personalities become better and more useful in the future. One of the government's efforts in education is related to the development of students, so guidance and counseling education is made as a path of assistance or a place for stories of students in the process of their development. The purpose of this research is to describe the psychological and psychosocial picture of children who are victims of parental divorce. This study uses a qualitative research approach with a case study type of research. The data collection method used was observation, interviews using a case study stage with 3 respondents who had a background in divorce from their parents with different cases. The results and discussion of this study show a negative impact psychologically and psychosocially.